(untitled) (Symposium on Natural and Applied Sciences, 2026)
After achieving independence, our rich philosophical heritage was revived under the name “Uzbek Philosophy,” acquiring new meaning and content and entering a stage of modern development. This process, associated with returning philosophy to its essence, gradually eliminating the remnants of past eras, and emphasizing renewal, change, and development, became an integral part of the spiritual and educational life of our society. It also underscored the necessity of developing national philosophy to shape contemporary thinking among our people.